Labor Day - Reitman, Jason, 1977-; Halfon, Lianne; Smith, Russell, 1954-; Estabrook, Helen; Winslet, Kate; Brolin, Josh; Griffith, Gattlin; Maguire, Tobey, 1975-; Maynard, Joyce, 1953-; Paramount Pictures Corporation; Indian Paintbrush (Firm); Right of Way Films (Firm); et al. (Hollywood, California : Paramount Pictures, 2014)
Thirteen-year-old Henry Wheeler struggles to be the man of his house and care for his reclusive mother Adele, all the while confronting the pangs of adolescence. Henry and his mother encounter Frank Chambers, an intimidating man clearly in need of help. Frank convinces them to take him into their home and later is revealed to be an escaped convict. The events of this long Labor Day weekend will shape them for the rest of their lives.
DVD, NTSC, region 1, widescreen presentation (enhanced for 16:9 TVs); 5.1 Dolby Digital.
In English, dubbed French, or dubbed Spanish; English, French, Spanish, or Portuguese subtitles; closed-captioned; English audio description track for people with visual disabilities.
Title from disc surface.
Kate Winslet, Josh Brolin, Gattlin Griffith, Tobey Maguire.
Music, Rolfe Kent ; film editor, Dana E. Glauberman ; producion designer, Steve Saklad ; director of photography, Eric Steelberg.
Originally released as a motion picture in 2013.
Keywords: Mothers and sons -- Drama; Teenage boys -- Drama; Life change events -- Drama; Recluses -- Drama; Fugitives from justice -- Drama; Betrayal -- Drama; Feature films; Romance films; Film adaptations; Coming-of-age films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities